2018
DOI: 10.3390/soc8020039
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Hopelessness among Turkish Elderly People Living with Family or in Nursing Homes

Abstract: The aim of the current study was to examine the prevalence and socio-demographic correlates of hopelessness among Turkish elderly people. A convenience sample of 100 elderly people (51 women, 49 men) living in a city in the central Black Sea region of Turkey completed the Beck Hopelessness Scale and a data collection instrument to identify their socio-demographic information. The data was analyzed using Chi-Square, Pearson correlation, and hierarchical multiple regression analysis. The study results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The disposable income of these households remained at or below the edge of social minimum (minimum income standard). In other studies [66,67], a particularly difficult life situation of the elderly living in rural areas was also noticed. Older people living in the countryside are often left alone, relying on the help of their neighbors, local authorities and occasional visiting family "from the city" or become a burden and trouble for the family remaining in the village.…”
Section: Discussionmentioning
confidence: 61%
“…The disposable income of these households remained at or below the edge of social minimum (minimum income standard). In other studies [66,67], a particularly difficult life situation of the elderly living in rural areas was also noticed. Older people living in the countryside are often left alone, relying on the help of their neighbors, local authorities and occasional visiting family "from the city" or become a burden and trouble for the family remaining in the village.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, it was found that the hopelessness levels of the older adult population who were not infected during the outbreak period were below the middle level. Sarin et al ( 2016 ) found in their study that the hopelessness level of older adults was moderate, Şahin et al ( 2018 ), Choi et al ( 2016 ) stated that older adults have high levels of hopelessness. The fact that this research was conducted during the COVID-19 outbreak is thought to have an impact on the level of hope.…”
Section: Discussionmentioning
confidence: 97%
“…Koenig stated that spirituality is a powerful source of hope and is effective in reducing despair (Koenig, 1994 ). Considering the negative effects of hopelessness on the immune system, it is thought that supporting older adults spiritually may reduce the long-term mental consequences of the COVID-19 outbreak (Şahin et al, 2018 ; Koening, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For those left behind losing a partner is traumatic. It can exacerbate health issues, increase the risks of morbidity and mortality, and evokes feelings of loneliness and social isolation [14] [46][51] [27] [15], desolation [28] [16], and incessant yearning for the lost affection of their beloved [39] [47] [48]. It may even lead to further mental health issues [38][44] [23] [45].…”
Section: Introductionmentioning
confidence: 99%